Brains Unlimited: Giftedness and Gifted Education in Canada before Sputnik (1957) - Ellis, Jason (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
This study’s purpose is to sketch, using the historical method, the development of ideas about giftedness and programs for gifted children in Canadian schools, from the nineteenth century to the launch of the Soviet satellite Sputnik in 1957 that reignited interest in gifted education. The author notes that historians have paid scant attention to giftedness. The author argues that giftedness and gifted education in Canada developed in three historical phases prior to 1957. Rationales for gifted education today are discussed in light of the historical legacy.